Catalysing the Scale-Up of Integrated Small Ruminant Value Chains in Eastern and Southern Africa - Recha, John W.M.; Demissie, Teferi; Haile, Aynalem; Mengistu, Tesfaye G; Makonnen, Brook T.; Ambaw, Gebermedihin; Barungi, Julian; Magagula, Futhi; Taapopi, Mirjam; Gitau, Angela; Johnston, Angharad; Varley, Ciara; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Ruminant livestock play pivotal roles in African economies and societies, linking multiple value chains that influence food security, nutrition, and livelihoods. Among the dryland communities of Eastern and Southern Africa, small ruminants – primarily goats and sheep – serve as critical livelihood assets, especially for women and youth. However, animal productivity remains low due to inbreeding, inadequate genetic monitoring, poor feeding, and limited access to veterinary care. Community-Based Breeding Programs (CBBPs), co-developed by CGIAR and local farmers, present a participatory, scalable, and cost-effective approach to addressing some of these challenges. By improving local breeds of small ruminants and enhancing adaptive capacity, CBBPs strengthen climate resilience, bolster productivity, and contribute to marginalized populations' economic and nutritional well-being, particularly in rural areas. This report presents insights from a regional learning event organized by ASARECA and CCARDESA under the AICCRA and LEG4DEV projects, in partnership with ICARDA, ILRI, and the Ethiopian Institute of Agricultural Research (EIAR). The learning event brought together 148 Ethiopian livestock keepers – including 47 women – from the Bonga area, along with 26 international participants comprising women and youth livestock keepers, livestock specialists, and extension staff from Kenya, Uganda, Burundi, Botswana, and Namibia. Through a combination of theoretical instruction and practical field demonstrations, participants strengthened their capacities in livestock reproductive technologies, forage production, and livestock agribusiness. A follow-up visit to digital livestock market actors in Addis Ababa provided valuable exposure to private-sector innovations. The event demonstrated the potential of scaling Community-Based Breeding Programs (CBBPs) to transform small ruminant value chains, enhance climate resilience, and foster regional collaboration. The participating countries committed to initiating similar innovations within their national contexts, signaling momentum toward broader adoption of the CBBP approach across Africa.